When cross -multiplying, then this is fairly easy:
\(\displaystyle \dfrac{26}{x} = \dfrac{20}{x -3}\)
\(\displaystyle 20x = 26(x - 3)\)
\(\displaystyle 20x = 26x - 78\)
\(\displaystyle -6x = -78\)
\(\displaystyle x = 13\)
But what if we multiplied each term in the original problem by the \(\displaystyle LCD\) of \(\displaystyle x(x - 3)\)?
How would we go about that? If the \(\displaystyle LCD\) was only say \(\displaystyle (x - 3)\), then that would be easy. Even a situation with a \(\displaystyle LCD\) of something like \(\displaystyle (x + 6)(x - 3)\) would be easy of some canceling out scheme was going on.
Let's start out with the \(\displaystyle LCD\) method:
\(\displaystyle x(x -3)\dfrac{26}{x} = x(x - 3)\dfrac{20}{x -3}\)
What would be the next step?
\(\displaystyle \dfrac{26}{x} = \dfrac{20}{x -3}\)
\(\displaystyle 20x = 26(x - 3)\)
\(\displaystyle 20x = 26x - 78\)
\(\displaystyle -6x = -78\)
\(\displaystyle x = 13\)
But what if we multiplied each term in the original problem by the \(\displaystyle LCD\) of \(\displaystyle x(x - 3)\)?
How would we go about that? If the \(\displaystyle LCD\) was only say \(\displaystyle (x - 3)\), then that would be easy. Even a situation with a \(\displaystyle LCD\) of something like \(\displaystyle (x + 6)(x - 3)\) would be easy of some canceling out scheme was going on.
Let's start out with the \(\displaystyle LCD\) method:
\(\displaystyle x(x -3)\dfrac{26}{x} = x(x - 3)\dfrac{20}{x -3}\)
What would be the next step?